2013
DOI: 10.2166/wst.2013.774
|View full text |Cite
|
Sign up to set email alerts
|

Removal kinetic of Escherichia coli and enterococci in a laboratory pilot scale wastewater maturation pond

Abstract: During the last 15 years several authors studied the disinfection in waste stabilisation pond (WSP) and several empirical models were developed. There are huge differences between the models describing this process and there is really a need to improve the design of ponds for better disinfection. This paper addresses the Escherichia coli and enterococci disinfection in a laboratory pilot scale maturation pond (1.5 l) with light intensity (0, 12 and 25 W/m(2)) under controlled pH, temperature and dissolved oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
8
7
0
Order By: Relevance
“…In this four-year full-scale WSP study, the removal efficiencies of E. coli may increase with increasing temperature. This observation is consistent with a number of studies that have reported increased removal efficiencies of fecal coliforms with increasing temperature [25,[34][35][36][37][38]. It should be noted that effects of hydraulic retention [39,40], hydraulic efficiency [39,40], sunlight [3], attachment/sedimentation [9], predation and nutrient availability may all contribute to It should be noted that effects of hydraulic retention [39,40], hydraulic efficiency [39,40], sunlight [3], attachment/sedimentation [9], predation and nutrient availability may all contribute to disinfection in WSPs.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In this four-year full-scale WSP study, the removal efficiencies of E. coli may increase with increasing temperature. This observation is consistent with a number of studies that have reported increased removal efficiencies of fecal coliforms with increasing temperature [25,[34][35][36][37][38]. It should be noted that effects of hydraulic retention [39,40], hydraulic efficiency [39,40], sunlight [3], attachment/sedimentation [9], predation and nutrient availability may all contribute to It should be noted that effects of hydraulic retention [39,40], hydraulic efficiency [39,40], sunlight [3], attachment/sedimentation [9], predation and nutrient availability may all contribute to disinfection in WSPs.…”
Section: Resultssupporting
confidence: 93%
“…In this four-year full-scale WSP study, the removal efficiencies of E. coli may increase with increasing temperature. This observation is consistent with a number of studies that have reported increased removal efficiencies of fecal coliforms with increasing temperature [25,[34][35][36][37][38].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations